Historiography and historical sources on the reception of pestalozzi in cuba (1807-1948) - Cordoví Núñez, Yoel (Historia y Memoria de la Educación, 2024)
The aim of this text is to explore the reception and circulation of the intuitive method in Cuba, and of Pestalozzi’s pedagogy, between 1807 and 1958 - a subject virtually untouched by Cuban historical research. The time frame spans from the entrance of the first references to the Pestalozzian proposals in the Antillean colony, to the death of Alfredo Miguel Aguayo, the pedagogue who contributed most in Cuba to the knowledge of Pestalozzi’s method. The central question is: What are the possible historical sources available to analyze the dissemination of the Pestalozzian pedagogical proposals in Cuba? The article touches upon the main institutions and authors whose works refer to the Pestalozzian pedagogical philosophy. In particular, the article highlights the role of the Sociedad Económica de Amigos del País (Economic Society of Friends of the Country), founded in Havana in 1793, in the introduction and promotion of Pestalozzi’s method. It also examines the pedagogical ideas of influential educators such as José de la Luz y Caballero (1800-1862), Manuel Valdés Rodríguez (1849-1914) and Alfredo Miguel Aguayo (1866-1948). Moreover, it considers the normative documents that, in the different contexts, prescribed the adaptation of the method to the Cuban school scenarios -namely, the colonial period (1807-1898), the US-military occupation (1899-1902), and after the establishment of the republic (1902-1958).